2018
DOI: 10.37358/rc.18.5.6257
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Antioxidant Activity of Aqueous Extracts Obtained from Herb of Tansy (Tanacetum Vulgare L.)

Abstract: The aim of this study was to determine the phenolic content and antioxidant activity of extracts obtained from herb of Tanacetum vulgare L. (tansy) harvested in two different locations from the western part of Romania. Aqueous extracts of tansy presented high antioxidant activity that ranged between 295.77 and 653.65 mg GAE/L, and remarkable percentage of inhibition (31.82-65.05 %). The compounds quantified in the plant extracts that were determined by UHPLC are: ascorbic acid, riboflavin, pyrocatechol, rutin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
(20 reference statements)
2
6
0
Order By: Relevance
“…group of secondary metabolites and play a key role in plant defense against fungal and bacterial pathogens [Jamiołkowska and Kopacki 2019]. Polyphenolic compounds are widely present in many plant species, including yarrow flowers [Devrnja et al 2017, Ivănescu et al 2018, Mot et al 2018, Kaczorová et al 2021.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…group of secondary metabolites and play a key role in plant defense against fungal and bacterial pathogens [Jamiołkowska and Kopacki 2019]. Polyphenolic compounds are widely present in many plant species, including yarrow flowers [Devrnja et al 2017, Ivănescu et al 2018, Mot et al 2018, Kaczorová et al 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Not only flavonoids, but also essential oils and their composition determine the antimicrobial effect of tansy plant [Vilhelmova et al 2020]. Chlorogenic [Ivănescu et al 2018] and cichoric acids [Bączek et al 2017] are the main phenolic compounds found in tansy extracts, and the variation in the composition of bioactive compounds in the extracts and essential oils depends on the geographical [Mot et al 2018].…”
Section: Resultsmentioning
confidence: 99%
“…The phenolic fraction is more abundant in tansy extracts respect to thyme ones because flowers were present in tansy sample used, while thyme sample contained only leaves. A very recent study on antioxidant activity of tansy shows that flowers extract has a higher total phenolic content with a consequently higher antioxidant activity (Anca Mot et al, 2018).…”
Section: H-nmr Spectramentioning
confidence: 99%
“…From the results showed above is deducted that by the two types of electrochemical methods using screenprinted carbon electrodes (DPV and CV) and Jenco microelectrodes (for iodide detection), iodide can be easily determined qualitatively and quantitatively. Both methods are safe and easy to use, and can be thought of as a portable system with a wide range of applicability [34][35][36][37][38][39][40] (screen electrodes are already used to detect toxic and bioactive compounds in the life sciences), alongside other validated methods for the same purpose [41][42][43][44][45][46][47]. Redox microelectrodes correlate in a good manner the redox status of the solution with KI concentration.…”
Section: B2 Redox Microelectrodementioning
confidence: 99%